Herrenvolk-bloed vir die Afrikaner : veertig jaar Duitse weeskinders 1948-1988 (Historia, 2021)
""Herrenvolk blood"" for the Afrikaner: the German orphans reappraised after forty years. Had the founders of the so-called Dietse Kinderfonds (DKF) succeeded in their plan to bring 10000 German orphans to South Africa after World War II, it is quite conceivable that the fortieth anniversary of their coming to South Africa this year would have overshadowed such events as the tricentennial of the French Huguenots or the 150th commemoration of the Great Trek. However, as events turned out, only 83 German children were brought to South Africa under the auspices of the DKF thus reducing the historical significance of the event in relation to the mainstream of South African history.The purpose of this article is to show why some Afrikaners held Germany in such high esteem that they were prepared to do everything in their power to ensure that the Afrikaners would benefit from Germany's defeat in 1945 by obtaining for the volk some of the ""valuable blood of the German Herrenvolk"". It is argued that the Afrikaner's perception of Germany played a very important role in his struggle against British domination, and that many prominent Afrikaners including Genl J.B.M. Hertzog, Dr H.F. Verwoerd and Dr D.F. Malan, viewed Germany as the only possible safeguard against what they believed would be the inevitable total domination of the Afrikaner by the British. For this reason these people, and for that matter most Afrikaner nationalists, saw German immigration to this country as one way of counteracting British influence. With the rise of Hitler's Nazi state many Afrikaners favoured close cooperation with Germany and believed that that country would help them to re-establish the independence of the former Boer republics. Some organizations such as the Nuwe Orde and the Ossewa-Brandwag even favoured a Nazi like type of volkstaat for South Africa. It is therefore not surprising that these people were shocked, and even felt betrayed by the Smuts government, when Germany was defeated in 1945. The idea to bring German orphans to this country was therefore a kind of protest against the defeat of Germany and against South Africa's participation in the war on the side of Britain. Furthermore, most of the founding members of the DKF were staunch members of either the Nuwe Orde or the Ossewa Brandwag.
Keywords: Dietse Kinderfonds; German orphans; Children